Italian Cinema Audiences. Histories and Memories of Cinemagoing in Post-War Italy, de Daniela Trevery Gennari, Catherine O’Rawe, Danielle Hipkins, Silvia Dibuteilo y Sarah Culhane - Broitman, Ana; Kriger, Clara Beatriz; Castro, Valentina; Salas, Pablo (Imagofagia, 2021)
Sobre Daniela Treveri Gennari, Catherine O’Rawe, Danielle Hipkins, Silvia Dibeltulo y Sarah Culhane. Italian Cinema Audiences. Histories and Memories of Cinemagoing in Post-War Italy. New York: Bloomsbury Academic Publishing, 2020, 218 pp., ISBN: 978-1-5013-4769-6.